How can hotel smartphone apps enhance hotel guest experiences? An integrated model of experiential value. (19th November 2021) - Kim, Hyeongmin; Huh, Chang; Song, Chanho; Lee, Myong Jae
Abstract : Purpose: The purpose of this study was to investigate relationships among the experiential value of hotel apps, the cognitive and affective evaluation of hotel apps users, hotel apps users' satisfaction and their endorsement for the hotel apps. Specifically, this study examined the relationships that enhance hotel guests' experiences through hotel apps. Design/methodology/approach: The measurement items were developed through extensive literature review. This study used a web-based survey to test an integrated model of the experiential value. With a total of 320 usable samples, partial least squares structural equation modeling was carried out to identify key "driver" constructs and validate the proposed model. Findings: A significant relationship was found in the playfulness of hotel apps and hotel guests' cognitive and affective evaluations of the hotel apps, which positively influence hotel guests' satisfaction and their endorsement for the hotel apps. Hotel apps should create fun and entertainment features in the hotel apps so that the users of hotel apps can be enjoyable during their usage. In addition, providing hotel apps users with time saving and easy use of the hotel apps can affect their satisfaction and endorsement for the hotel apps. Originality/value: This study confirmed the positive links among hotel apps users' experiential value, their cognitive and affective evaluation of the hotel apps, their satisfaction of using the hotel apps and their endorsement for the hotel apps. This study also revealed that hotel apps can be hotels' effective communication tool that enhances existing and potential customers' overall experiences. Abstract : 酒店智能手机app如何提高用户体验？: 项关于体验价值的综合模型 摘要 研究目的: 本论文旨在研究关于酒店APP体验价值, 对酒店APP用户的认知和情感评估, 用户满意度以及用户支持之间的关系。具体而言, 本研究探索了如何通过酒店手机APP使用来提高用户体验的理论关系。 研究设计/方法/途径: 测量条目通过详尽的文献综述来产生。本研究运用了网络调研来测量体验价值的一项综合模型。由320项有效样本, 偏最小二乘法结构方程建模（PLS-SEM）来鉴定关键"驱动"构象以及验证提出的模型。 研究发现: 研究发现酒店APP的娱乐性对顾客的APP的认知和情感评估都起到了显著性作用, 进而对顾客满意度和酒店APP支持度产生正面影响。研究建议酒店APP创造有趣以及娱乐产品功能, 从而让酒店APP用户从使用中获得乐趣。此外, 为酒店APP用户提供省时方便的服务可以影响用户满意度和对酒店APP的支持。 研究原创性/价值: 本研究验证了酒店APP用户体验价值, 对酒店APP的认知和情感评估, 用户对使用酒店APP的满意程度, 以及对酒店APP支持的正相关性。本研究进而发现酒店APP可以作为提升酒店现有和未来用户全面体验的有效工具.